Characterization of Malassezia Species on the Healthy Skin of High School Students - Priscila Fernández; Evelyn González de Morán; María Lucía Delmonte; Sandra Robertiz (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2014)
The genus Malassezia includes a group of lipophilic yeasts that form part of the microbiota of the skin of humans and other vertebrates. Nevertheless, they have been related to several dermatological entities. This research proposed to characterize the morfophysiological Malassezia species isolated on the healthy skin of students at the Baralt High School in the city of Maracaibo, State of Zulia. Samples were taken using the imprint method with adhesive transparent tape on the scalp, pinna, chest and back, inoculated into a modified Dixon Agar medium and incubated at 32°C for 14 days. Identification of the species was carried out following the keys described by Gueho and Cols, the diffusion in tween test proposed by Guillot and collaborators, the catalase test and the utilization of triptophan as the only source of carbon. Out of a total of 100 evaluated students, 81 (81%) were positive for Malassezia and 184 isolations were obtained; 100 (54.30%) were of the masculine sex and 81 (45.6%) were females. The results show a high prevalence of Malassezia furfur (54.3%) followed by Malassezia sympodialis (45.1%) and finally, Malassezia globosa (0.50%). Anatomical locations with the greatest number of isolations were the back (33%) and chest (30.2%).